Delegating Pricing Power to Customers: Pay What You Want or Name Your Own Price? - Florentin Krämer; Klaus M. Schmidt; Martin Spann; Lucas Stich (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Pay What You Want (PWYW) and Name Your Own Price (NYOP) are customer driven pricing mechanisms that give customers (some) pricing power. Both have been used in service industries with high fixed costs to price discriminate without setting a reference price. Their participatory and innovative nature gives rise to promotional benefits that do not accrue to posted-price sellers. We explore the nature and effects of these benefits and compare PWYW and NYOP using controlled lab experiments. We show that PWYW is a very aggressive strategy that achieves almost full market penetration. It can be profitable if there are promotional benefits and if marginal costs are low. In contrast, NYOP can be used profitably also if marginal costs are high and if there are no such benefits. It reduces price competition and segments the market. In a second experiment, we generate promotional benefits endogenously. We show that PWYW monopolizes the follow-up market but fails to be profitable. NYOP is less successful in penetrating the market but yields much higher profits.
Keywords: D03; D21; D22; D40; L11; M31; 330; Customer-driven pricing mechanisms; pay what you want; name your own price; competitive strategies; marketing; laboratory experiment